2019
DOI: 10.1515/ijamh-2018-0094
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of and compliance to iron supplementation under the National Iron Plus Initiative among reproductive age-group women in urban Puducherry – a cross-sectional study

Abstract: Background Anaemia is a global health problem and an important cause of morbidity in all age groups, especially among women and children. Various programmes have been implemented to combat anaemia in India and National Iron Plus Initiative (NIPI) is the latest programme to be implemented. Aim To ascertain the proportion of reproductive age women receiving iron supplementation under the NIPI and assess the compliance and factors hindering the implementation and compliance of the programme. Materials and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…A cross-sectional study evaluating the compliance of the NIPI program among a group of reproductive aged (15–49 years) females in Puducherry found that only 45.7% of them were receiving the supplements under the NIPI program ( 27 ). Among the women who received supplementation, only 61% reported compliance ( 27 ). A qualitative study in Odisha showed the necessity of monitoring and evaluation to strengthen the implementation of the NIPI program ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study evaluating the compliance of the NIPI program among a group of reproductive aged (15–49 years) females in Puducherry found that only 45.7% of them were receiving the supplements under the NIPI program ( 27 ). Among the women who received supplementation, only 61% reported compliance ( 27 ). A qualitative study in Odisha showed the necessity of monitoring and evaluation to strengthen the implementation of the NIPI program ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study that evaluated the NNAC program in the Dharwad taluk also found an issue of irregular supply of the supplements (26). A cross-sectional study evaluating the compliance of the NIPI program among a group of reproductive aged (15-49 years) females in Puducherry found that only 45.7% of them were receiving the supplements under the NIPI program (27). Among the women who received supplementation, only 61% reported compliance (27).…”
Section: Iron Supplementation and Childhood Anemiamentioning
confidence: 99%
“…Data were collected through a structured and pretested questionnaire developed through a series of focus group discussions with subject experts (two pharmacologists, two clinical pharmacists, and one obstetrics/gynecology specialist) and a review of the literature. [ 10 11 12 13 14 15 16 17 18 19 ] The questionnaire was prepared in English, translated into Tamil and then translated back into English for the accuracy of translation. There was pilot testing before the administration to the participants.…”
Section: Methodsmentioning
confidence: 99%
“…Adherence is defined by the WHO as “the degree to which the person's behavior corresponds with the agreed recommendations from a healthcare provider.”[ 9 ] Although studies have been conducted to assess adherence to IFAS in different regions of India,[ 10 11 12 13 ] only one study has evaluated the implementation of NIPI in urban Puducherry,[ 14 ] our region of interest. Moreover, although direct monitoring of IFAS[ 11 15 16 ] and appropriate counseling[ 16 17 18 ] have been reported to be crucial for achieving positive outcomes, no study investigating these variables specifically has been conducted in Puducherry.…”
Section: Introductionmentioning
confidence: 99%
“…Bleeding after childbirth is the primary cause of death as a result of anemia (Astapani, Harahap Anggriani, 2020). Generally, anemia occurs due to iron deficiency (Gayathri et al, 2021). Anemia in pregnancy affects the mother and fetus.…”
Section: Introductionmentioning
confidence: 99%